2003
DOI: 10.1023/b:jopc.0000005460.94172.1d
|View full text |Cite
|
Sign up to set email alerts
|

Hypochlorite Action on Plasma Fibronectin Promotes Its Extended Conformation in Complexes with Antibodies

Abstract: We investigated the influence of hypochlorite (HOCl/OCl-) on plasma fibronectin (Fn) aggregation and examined an affinity of Fn aggregates to Fn specific antibodies. Human plasma Fn HOCl/OCl(-)-mediated modification was monitored with differential OD method and with measurements of tryptophan fluorescence followed by acrylamide quenching of tryptophan emission. Antibody fibronectin complex formation was examined in ELISA systems with chemiluminescence (CL) detection. Results were expressed as an average of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, analysis of such data can be complex, as damage may also enhance antibody binding by exposing cryptic epitopes. Thus, low doses of HOCl appear to increase the affinity of anti-fibronectin antibodies to plasma fibronectin, whereas high concentrations have the opposite effect (87). This has been rationalized in terms of the generation of an extended fibronectin conformation at low HOCl doses, and aggregation with high concentrations.…”
Section: Gross Modification Of Parent Proteinsmentioning
confidence: 98%
“…However, analysis of such data can be complex, as damage may also enhance antibody binding by exposing cryptic epitopes. Thus, low doses of HOCl appear to increase the affinity of anti-fibronectin antibodies to plasma fibronectin, whereas high concentrations have the opposite effect (87). This has been rationalized in terms of the generation of an extended fibronectin conformation at low HOCl doses, and aggregation with high concentrations.…”
Section: Gross Modification Of Parent Proteinsmentioning
confidence: 98%
“…These only occurred in the presence of H 2 O 2 , and hence are not a result of direct MPO binding, and therefore are likely to arise from oxidant-induced reactions. HOCl can modify specific protein side chains, resulting in unfolding or altered protein conformations, that migrate differently on gels, and thereby appear to have an altered molecular mass [ 16 , 77 ]. Oxidation can also increase the molecular mass of proteins as a result of (multiple) oxygen or chlorine atom incorporation [ 78 ], but the apparent mass changes are large, and hence unlikely to arise from this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the distribution of electrostatic forces stabilizing the protein structures is probably different in the plasma and cerebrospinal fluid. Some in vitro experiments show that native fibronectin can undergo dramatic structural changes from a globular to an extended conformation after treatment with low doses of hypochlorite (Olszowski et al, 2003), or after urea-induced denaturation (Lairez et al, 2003;Patel et al, 2006;Nelea et al, 2008). In such cases the accessibility of fibronectin epitopes for an antibody increases.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases the accessibility of fibronectin epitopes for an antibody increases. Olszowski et al (2003) have shown that the number of accessible fibronectin epitopes increases when fibronectin adopts an extended conformation in complex with the antibody. In our experiment under the mildly denaturing conditions of 0.5-2 M urea, the hidden epitopes of the N-terminal and some of the CBD domains were probably exposed and made more accessible for reaction with the respective antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation